The Effect of Work Motivation and Discipline on The Performance of The Leading Teachers of Madrasah - Suprihatin, Suprihatin; Rachmawati, Diana Widhi; Sasongko, Rambat Nur; Ma`arif, Muhammad Anas; Khadafi Kader, Muhammad Anshar (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This article aims to determine the effect of motivation and work discipline on MA Unggulan Hikmatul Amanah Pacet. Respondents in this study were all teachers of the Supreme Court of Hikmatul Amanah Pacet, totaling 39 people. The results of the study found that: 1) The effect of work motivation on the performance of MA Hikmatul Amanah teachers was 23.9%, with a research t value of 1.589 < t table of 1.687 and a significant value of 0.121 > 0.05; 2) The effect of work discipline on Hikmatul Amanah's teacher performance was 40.9% with a research t value of 2.717 > t table of 1.687 and a significant value of 0.010 <0.05; 3) The simultaneous influence of motivation and work discipline on the performance of MA Hikmatul Amanah teachers is 19.8%, with a research F of 4.449 > F table of 3.25. The influence of motivation and work discipline on teacher performance at MA Wisdom Amanah Pacet needs to be considered. Solutions to the problem are sought to be more helpful in improving teacher performance in the future.